Advances in sulfur mustard-induced DNA adducts: Characterization and detection. (15th June 2021) - Cheng, Xi; Liu, Changcai; Yang, Yang; Liang, Longhui; Chen, Bo; Yu, Huilan; Xia, Junmei; Liu, Shilei; Li, Yihe
Highlights: Documentation of SM-DNA adducts detected by LC–MS/MS technology. Characterization of SM-induced biomarkers to help understand SM toxicity mechanism. Indication of other potential DNA adducts induced by SM and its secondary effects. Abstract: Sulfur mustard (SM) is a blister chemical warfare agent with severe cytotoxicity and genotoxicity. It can extensively alkylate important macromolecules in organisms, such as proteins, DNA, and lipids, and produce a series of metabolites, among which the characteristic ones can be used as biomarkers. The exact toxicological mechanisms of SM remain unclear but mainly involve the DNA lesions induced by alkylation and oxidative stress caused by glutathione depletion. Various methods have been used to analyze DNA damage caused by SM. Among these methods, liquid chromatography-tandem mass spectrometry (LC–MS/MS) technology stands out and makes it possible to observe damage in view of biomarkers induced by SM. Sample preparation is critical for detection by LC–MS/MS and mainly includes DNA isolation, adduct hydrolysis, and adduct purification. Moreover, optimization of chromatographic conditions, selection of MS transitions, and quantitative strategies are also essential. SM-DNA adducts are generally considered to be N 7 -HETEG, O 6 -HETEG, N 7 -BisG, and N 3 -HETEA. This article proposes some other possibilities of SM-DNA adducts for the identification of SM genotoxicity.